192k views
1 vote
How to find the derivative of the below question?


How to find the derivative of the below question? ​-example-1
User Dmidz
by
5.1k points

1 Answer

7 votes

Given:


y=(x)/(√(x-1))

To find:

The derivative of the given problem.

Solution:

Chain rule :
(d)/(dx)f(g(x))=f'(g(x))\cdot g'(x)

Quotient rule :
(d)/(dx)\left((f(x))/(g(x))\right)=(g(x)f'(x)-f(x)g'(x))/([g(x)]^2)

We have,


y=(x)/(√(x-1))

Differentiating with respect to x using chain rule and quotient rule, we get


(dy)/(dx)=(√(x-1)(d)/(dx)(x)-x(d)/(dx)(√(x-1)))/((√(x-1))^2)


(dy)/(dx)=(√(x-1)(1)-x(1)/(2√(x-1))(d)/(dx)(x-1))/((x-1))


(dy)/(dx)=(√(x-1)-(x)/(2√(x-1))(1-0))/(x-1)


(dy)/(dx)=(√(x-1)-(x)/(2√(x-1)))/(x-1)


(dy)/(dx)=\frac{\frac{2x-2-x}{2(x-1)^{(1)/(2)}}}{(x-1)}


(dy)/(dx)=\frac{x-2}{2(x-1)^{(3)/(2)}}

Therefore, the required derivative is
(dy)/(dx)=\frac{x-2}{2(x-1)^{(3)/(2)}}.

User Erik Bender
by
4.7k points